Effects of Kalsis, A Dietary Supplement, on Bone Metabolism in the Ovariectomized Rats - Mercedes Montero; Manuel Díaz-Curiel; David Guede; Jose Ramón Caeiro; Marta Martín-Fernández; Mercedes Rubert; Daisy Navarro; Concepción de la Piedra (Journal of Osteoporosis)
We studied the ability of Kalsis, a food supplement that contains selenium, citric acid, and vitamin E, to prevent the effects of ovariectomy on bone loss. Six-month-old, Wistar female rats were studied. Groups (n=12): SHAM: sham-operated rats; OVX: ovariectomized rats, treated with vehicle; OVX + Kalsis: ovariectomized rats treated with Kalsis (25 mg/kg/day) for 3 months. Bone mineral density (BMD) was determined by DXA in lumbar spine and femur. Computerized microtomography (μCT) in femur and serum osteocalcin (BGP), aminoterminal propeptide of procollagen I (PINP), β-isomer of carboxyterminal telopeptide of collagen I (CTX), and 5b isoenzyme of tartrate-resistant acid phosphatase (TRAP) were performed. Treatment with Kalsis prevented BMD loss in OVX group. μCT showed a decrease in BV/TV, and trabecular number, and an increase in trabecular separation in OVX rats. Kalsis administration attenuated partially bone loss observed by μCT due to ovariectomy. BGP, PINP, and the resorption index (CTX/TRAP) were increased in OVX group. Treatment with Kalsis maintained this increase. The mechanism of action of this supplement is not through a decrease in bone remodelling rate. The antioxidant action of this food supplement, due to the synergism of all its components, as a cause of its beneficial effect is suggested.